SEROMA FORMATION AND ITS RELATIONSHIP WITH MECHANICAL DEAD SPACE OBLITERATION FOLLOWING MODIFIED RADICAL MASTECTOMY - RENJIN RP; JOMINE JOSE; ANISH AV (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: Modified radical mastectomy (MRM), a common approach in breast cancer treatment, often leads to seroma formation, posing challenges to patient recovery. This retrospective study investigates the relationship between flap fixation and seroma formation, focusing on the obliteration of mechanical dead space. Our findings contribute valuable insights into minimizing postoperative morbidity and optimizing patient care. Methods: A retrospective analysis was conducted on 120 females undergoing MRM, with 60 patients undergoing conventional procedures and 60 with flap fixation. Patient characteristics, operation duration, drainage amount, removal time, flap necrosis, and infection rates were recorded and compared using t-tests. Results: Flap fixation demonstrated a significant reduction in drained serous fluid and duration of drain removal compared to the control group (p<0.001). Infection rates were comparable between the study (25%) and control (18%) groups (p=0.22). The study group showed a mean duration of drain removal of 11.18 days, significantly shorter than the control group’s 14.22 days (p<0.001). Conclusion: Flap fixation emerges as a promising technique in reducing seroma formation and addressing mechanical dead space after MRM. This study advocates for the adoption of flap fixation in routine surgical practice, offering surgeons an effective strategy to enhance postoperative recovery and minimize patient morbidity.